Special characteristics of the transcription and splicing machinery in photoreceptor cells of the mammalian retina - Derlig, Kristin; Gießl, Andreas; Brandstätter, Johann Helmut; Enz, Ralf; Dahlhaus, Regina (Cell and Tissue Research, 2015)
Chromatin organization and the management of transcription and splicing are fundamental to the correct functioning of every cell but, in particular, for highly active cells such as photoreceptors, the sensory neurons of the retina. Rod photoreceptor cells of nocturnal animals have recently been shown to have an inverted chromatin architecture compared with rod photoreceptor cells of diurnal animals. The heterochromatin is concentrated in the center of the nucleus, whereas the genetically active euchromatin is positioned close to the nuclear membrane. This unique chromatin architecture suggests that the transcription and splicing machinery is also subject to specific adaptations in these cells. Recently, we described the protein Simiate, which is enriched in nuclear speckles and seems to be involved in transcription and splicing processes. Here, we examine the distribution of Simiate and nuclear speckles in neurons of mouse retinae. In retinal neurons of the inner nuclear and ganglion cell layer, Simiate is concentrated in a clustered pattern in the nuclear interior, whereas in rod and cone photoreceptor cells, Simiate is present at the nuclear periphery. Further staining with markers for the transcription and splicing machinery has confirmed the localization of nuclear speckle components at the periphery. Comparing the distribution of nuclear speckles in retinae of the nocturnal mouse with the diurnal degu, we found no differences in the arrangement of the transcription and splicing machinery in their photoreceptor cells, thus suggesting that the organization of these machineries is not related to the animal's lifestyle but rather represents a general characteristic of photoreceptor organization and function.
EVALuna2:4722